2013
DOI: 10.1016/j.ejrad.2013.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between knee alignment and T1ρ values of articular cartilage and menisci in patients with knee osteoarthritis

Abstract: Objective To assess the relationship between knee alignment and subregional T1rho values of the femorotibial cartilage and menisci in patients with mild (Kellgren-Lawrence grade 1) to moderate (KL3) osteoarthritis (OA) at 3T. Materials and methods 26 subjects with a clinical diagnosis of KL1-3 OA were included and subdivided into three subgroups: varus, valgus, and neutral. All subjects were evaluated on a 3T MR scanner. Mann-Whitney and Wilcoxon signed rank tests were performed to determine any statisticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…40 Wang et al found higher T1ρ values on the medial anterior femur in OA patients with knee varus. 41 We suspected lateral and medial patellar translation to have a greater association with lateral and medial trochlear cartilage T1ρ values, respectively. However, additional explorative analyses in the current study with separate medial and lateral trochlear T1ρ relaxation times did not show a difference in the association with patellar translation between the lateral and medial compartment.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…40 Wang et al found higher T1ρ values on the medial anterior femur in OA patients with knee varus. 41 We suspected lateral and medial patellar translation to have a greater association with lateral and medial trochlear cartilage T1ρ values, respectively. However, additional explorative analyses in the current study with separate medial and lateral trochlear T1ρ relaxation times did not show a difference in the association with patellar translation between the lateral and medial compartment.…”
Section: Discussionmentioning
confidence: 89%
“…This is in line with other studies which have described a loss of cartilage thickness associated with knee malalignment . Wang et al found higher T1ρ values on the medial anterior femur in OA patients with knee varus . We suspected lateral and medial patellar translation to have a greater association with lateral and medial trochlear cartilage T1ρ values, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…4 In cohorts of less than 30 individuals, people with medial knee OA who had varus alignment were found to have higher cartilage T1rho and T2 than those with valgus alignment. 20,55 Most of these studies either were in healthy cohorts or had a small sample size. Longitudinal studies in larger samples, like the OAI cohort, are needed to understand the effect of these OA risk factors on cartilage degeneration over time.…”
Section: Discussionmentioning
confidence: 99%
“…T 1r -weighted imaging has been extensively used in the past decades to assess pathology of liver, muscle, breast, brain, and tumor (32,33,47,115,122,129,130,(132)(133)(134) besides those of human MSK system (9,34,36,38,44,47,53,(62)(63)(64)(65)(66)(67)(68)(69)(105)(106)(107)(108)(109)(110)124). These studies have demonstrated the potential values of T 1r imaging for evaluating various physiologic and pathologic states.…”
Section: Future Prospectsmentioning
confidence: 99%